Karakterisasi Dan Potensi Pengolahan Air Gambut Menggunakan Biosorben - Mahardika, Dewa Ayu Divia Pradhaswari; Andrio, David; Darmayanti, Lita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Peat water is surface water with striking characteristics because it has a high content of color and organic subtances, so it needs further processing so that it can be used as clean water. Adsorption using biosorbent is one method that has the potential to remove color and organic matter substances in peat water. This research aims to determine the characteristics of peat water and analyze the removal of colors and organic substances using biosorbent. The results of this study show the colors and organic substances in 1715 Pt/Co and 616,2 mg/l. Keywords: biosorbent, color, organic substances, peat water